Influence of school playground size and equipment on the physical activity of students during recess. (May 2016) - Delidou, Eleni; Matsouka, Ourania; Nikolaidis, Christos
Children's physical activity (PA) is increasingly restricted by the fast pace of modern life. Schools are the opportune setting in which to increase PA during daily recess. The purpose of this study was to record the degree of PA of 6th grade primary school students during recess and determine whether the playground size and available equipment can influence the degree of students' PA. The study sample comprised of 625 12-year-old students, 324 (51.8%) boys and 301 (48.2%) girls. The PA during recess was calculated by Metabolic Equivalent Time (MET*min) using a self-reference questionnaire. The impact of schoolyard size and equipment on MET*min was evaluated by Kruskal–Wallis analysis of variance (ANOVA). The students' PA (MET*min) during recess was higher at schools with a large schoolyard (197.55±133.15 MET*min), compared with medium size (152.65±109.23 MET*min) and small ones (117.69±104.22 MET*min), (χ 2 =50.629, p <0.001). Moreover, students were more physically active during recess in adequately equipped schools (187.11±124.21 MET*min), compared with partially (158.84±128.61 MET*min) or inadequately equipped ones (114.19±89.13 MET*min). This indicates a strong positive relationship between PA and equipment (χ 2 =21.277, p <0.001). An encouraging school environment can motivate pre-adolescent children to be more physically active and therefore healthier. These data reveal that spacious schoolyards rich in outdoor facilities can lead to more physically active behaviour among students during recess.